POSITIONING GEOPARK GUNUNG BATUR SEBAGAI DAYA TARIK EKOWISATA DI KINTAMANI, KABUPATEN BANGLI - Cintya Dewi, Luh Putu Vira; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 2 No 1 (2014): VOL 2, NO 1 (2014): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT Kintamani is an area that has natural beauty and unique culture. So the beauty of Kintamani tourism attraction is no stranger to tourists both foreign tourists and domestic travelers. Geo-park is a territory that includes one or more sites of scientific importance, not only for geological reasons but also by the value of archaeological, ecological or cultural. Geo- park initiative launched by UNESCO in response to the perceived need for an international initiative that recognizes the site represents the interests of earth sciences. Global geo park network program aims to increase the value of the site while at the same time create jobs and promote regional economic development. In this study using data collection methods such as observation, in-depth interviews, questionnaires and documentation. Respondent retrieval technique using purposive sampling. While the techniques of data analysis using qualitative descriptive analysis. In this study the results obtained, the tourist image of Batur Mount Geo- park, tourist imagery to amenities in Kintamani, tourist image of the accessibility and the tourist image of ancillary in Kintamani. Once known tourist image of the components of the tourism it is known to result from Batur Mount Geo-park positioning as an eco-tourism attraction in Kintamani, Bangli.
Keywords: Keywords: Geo-park, Image, and Positioning Batur Mount Geo-park.